Web Accessibility and Inclusion in Online National Population Censuses: Insights from Ecuador - Sandra Sanchez-Gordon; Arias Flores, Hugo Patricio; Mary Sánchez-Gordón (My University, 2024)
The creation of smart societies involves harnessing technological innovations to improve the quality of life of all citizens. Web accessibility and inclusion are fundamental pillars for achieving this goal. Population censuses provide demographic information that allows governments to develop public policies that address the specific needs of diverse communities. Although many countries have adopted population census strategies involving online questionnaires, implementation of online population censuses with web accessibility and inclusivity considerations has not been addressed in the scientific literature. While digitization of population censuses provides benefits, it can also exclude those facing online participation barriers. One of the challenges is the lack of web accessibility for citizens with disabilities. This exploratory study focuses on technical aspects and analyzes the web accessibility issues detected in the online population census conducted in Ecuador in 2022. In general terms, this online census did not comply with the Web Content Accessibility Guidelines (WCAG) 2.2, thus making interaction difficult for people with blindness, low vision, and limited movement, among other disabilities. Likewise, there are other issues related to data privacy and the inclusiveness of online censuses. People with disabilities and other underrepresented social groups may have limited access to devices and internet connections, reducing their ability to participate in online population censuses. This can cause a bias in the data collected, affecting the accurate representation of the population. In the case of Ecuador's 2022 population census, this might be the cause of a contradiction that arose between the data collected, the previous data, and the growth projections regarding the Afro-descendant population.
Keywords: accessibility; blindness; digital census; disabilities; inclusion; online census; privacy; sortSite; WAVE; WCAG; web accessibility evaluation tools; web content accessibility guidelines